Simulasi Jaringan Local Area Network Menggunakan Cisco Packet Tracer (Cisco Systems) - Putri Andini Maulana; Dewangga Andira Sulaeman; Andika Chaesar Destryana; Didik Aribowo (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
As time goes by, existing technology continues to develop, one of which is network communication technology. LAN Computer Network or Local Area Network is a computer network consisting of several computers connected to each other in a relatively small area such as a building, campus or office. This research was conducted to see how a LAN network works to deliver data or information. This research is a type of descriptive research. The methods used in this research are literature study and simulation methods. The simulation is carried out using the Cisco network application. As a result, the Cisco application can project the working principles of a LAN network.